A fuzzy decision support model for the evaluation and selection of healthcare projects in the framework of competition - Gavurova, Beata; Kelemen, Miroslav; Polishchuk, Volodymyr; Mudarri, Tawfik; Smolanka, Volodymyr (Frontiers in Public Health, 2023)
Our research is aimed at supporting decision-making regarding the financing of health care projects by structural funds, the policy of which involves reducing the development gap between different regions and countries of the European Union, as well as achieving economic and social cohesion. A fuzzy decision support model for evaluation and selection of healthcare projects should rank the project applications of the selected region, taking into account the investor's wishes regarding the regional coefficient in order to reduce the development gap in the regions. The model, on the one hand, evaluates project applications based on selected criteria, which are structured, weakly structured, or unstructured, and on the other hand, combines the level of health care development in the region. The obtained ranking increases the degree of validity of the decision regarding the selection of projects for financing by investors, taking into account the development of the region where the project will be implemented. At the expense of the EU structural funds, it is possible for a village, city, region or state to receive funds for modernization, development of the health care sector and all related processes. In order to minimize risks, it is necessary to have adequate support systems for decision-making in the assessment of project applications, as well as the regional pol-icy where the project will be implemented. The main goal of this study is to develop a complex fuzzy decision support model for the evaluation and selection of projects in the field of health care in order to reduce the development gap in the regions. From the above, we can form a scientific hypothesis of this research as follows. If the project selected for financing can successfully fulfill the declared goals and increase the level of development of its region, then it is possible to claim a high evaluation of the project, obtained based on a built complex fuzzy model that takes into account the development of the region in terms of the availability and quality of services in the field of health care, where the project will be implemented.